Letter to Jane Tolmach from Richard Nevins - Richard Nevins:::::: (1971)
In this January 8, 1971 letter, Richard Nevins invites Jane Tolmach to join him and Mary Lois for cocktails on January 22 at the Cosmopolitan El Mirador Hotel in Sacramento. The gathering is planned for the evening before an important Democratic State Central Committee meeting, offering an opportunity for friends to meet informally. Contact information is provided to RSVP.